Acculturation and activity behaviors in Chinese American immigrants in New York City - Yi, Stella S. (Prev Med Rep, 2016)
Asian Americans have lower levels of physical activity (PA) compared to other racial/ethnic groups; however, there is little understanding of the social and cultural determinants of PA in this population. Few analyses describe specific PA domains (occupation-, transportation-, recreation-related), focus on one Asian subgroup, or use validated scales. The study objective was to assess the association between acculturation and activity behaviors (meeting 2008 PA guidelines, activity minutes by PA domain, sitting time) in a cross-sectional sample of urban-dwelling, Chinese American immigrants. Data were from the Chinese American Cardiovascular Health Assessment (CHA CHA) 2010–11 among participants with valid reports of PA minutes, assessed by the WHO Global Physical Activity Questionnaire (n = 1772). Acculturation was assessed using the Stephenson Multigroup Acculturation Scale, a 32-item instrument which characterizes two acculturative dimensions: ethnic society (Chinese) immersion and dominant society (American) immersion (maximum possible scores = 4). Multivariable models regressing activity behaviors on acculturation were run, adjusting for age, sex, household income, education, and age at immigration. Ethnic society immersion was high (mean = 3.64) while dominant society immersion was moderate (mean = 2.23). Higher ethnic society immersion was associated with less recreation-related PA (− 40.7 min/week); higher dominant society immersion was associated with a higher odds of meeting PA guidelines (OR: 1.66 (1.25, 2.20), p < 0.001) and more recreation-related PA (+ 36.5 min/week). Given low PA levels in Chinese adults in China, results suggest that PA for leisure may increase and become a more normative behavior among Chinese American immigrants with acculturation. Understanding acculturation level may inform strategies to increase PA in Chinese Americans.